Removal of Pollutants from Secondary Waste from an Incineration Plant: The Review of Methods - Magdalena Bogacka; Nikolina Poranek; Beata Łaźniewska-Piekarczyk; Krzysztof Pikoń (Energies, 2020)
In order to use secondary waste from an incineration plant, it is necessary to process or treat it. Valorization of municipal solid waste incineration bottom ash (MSWIBA) is a popular treatment method. Moreover, there are other possibilities, such as alkaline pre-treatment, which can be used for the rest of the secondary waste from incineration plants, especially hazardous fly ash. The purpose of this study is to show the problem of secondary waste in Poland in relation to the rest of Europe. Due to the physicochemical research of secondary waste, the possibilities of the procedure and its management are indicated. By analyzing the literature and the market, the latest possibilities for improving the physicochemical properties of secondary waste are proposed. Searching for new methods for waste management is essential to the environment. This manuscript presents the problem of the increasing amount of waste, as well as possibilities to close the loop, and minimize the negative impact on the environment. Additionally, the article shows that environmental benefits can be achieved by replacing raw material with secondary waste.